2017
DOI: 10.25177/jcebc.2.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Phytochemical Characterization of Seed Kernel oil From Desert Date (Balanites Aegyptica)

Abstract: The seed oil of Balanites aegyptiaca was extracted and its physical, phytochemical and chemical properties which accounts for the oil quality parameters were investigated. The elemental composition of the oil revealed high metal concentration of sodium (5.9178±0.2 mg/g) in the seed kernel, magnesium (2.2242±0.007 mg/g) and calcium (1.4643±0.5) in the seed oil. The chemical parameters evaluated include saponification value (200.02±0.12 mgKOH/g), acid value (2.14±0.28 (mgKOH/g), iodine value (104.39±0.00 100/g),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
3
3
0
Order By: Relevance
“…Oils with acid value higher than 4 mg KOH / g tend to have a high percentage of free fatty acids, and are susceptible to rancidity due to the hydrolysis of the free fatty acids at storage conditions. Similar results were reported by Manji et al, (2013) and Jock (2017) on the acid value and the free fatty acid contents of the Aduwa seed oils; however, Ogala, et al, (2018) reported higher results.…”
Section: Seed Oilsupporting
confidence: 87%
“…Oils with acid value higher than 4 mg KOH / g tend to have a high percentage of free fatty acids, and are susceptible to rancidity due to the hydrolysis of the free fatty acids at storage conditions. Similar results were reported by Manji et al, (2013) and Jock (2017) on the acid value and the free fatty acid contents of the Aduwa seed oils; however, Ogala, et al, (2018) reported higher results.…”
Section: Seed Oilsupporting
confidence: 87%
“…This result agreed with that of Li et al (2022) who reported a significant variation in Fe, Zn, Ca, and Mg among Uglans mandshurica Kernel in China. Similar quantities of mineral elements were also observed in desert date kernel oil in Jos, Nigeria (Zang et al, 2017). However, higher mineral values were reported by Atasie and Akinhanmi (2009) in common edible oils in Nigeria (palm ke rnel oil).…”
Section: @The Author(s) 2024 Published By Cbioresupporting
confidence: 74%
“…Hassan et al (2021) also reported the presence of saponins, flavonoids, and alkaloids in the kernel oil of desert date. However, Zang et al (2017) reported the absence of these phytochemicals. The contradictions among the results could be a function of oil extraction methods used and screening techniques used for identifying the phytochemicals.…”
Section: Phytochemical Properties Of Desert Date Kernel Oil From Diff...mentioning
confidence: 99%
“…Therefore, the current study was conducted to evaluate the nutritional characteristics of four (4) wild fruits, namely Gardenia erubescens , Sclerocarya birrea, Diospyros mespiliformis, and Balanites aegyptiaca from Ghana. Literature search has shown that the fruits of G. erubescens , S. birrea, D. mespiliformis, and B. aegyptiaca have been characterized through the fruit or pulp [28,29,30] and seeds [31,32] in some parts of the world. Studies have provided some promising nutritional information especially on the proximate, mineral compositions [28,29,30] and vitamin C content [28,29] of one or more of these fruits.…”
Section: Introductionmentioning
confidence: 99%